2021
DOI: 10.1101/2021.06.29.450292
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cryo-EM structure of MukBEF reveals DNA loop entrapment at chromosomal unloading sites

Abstract: The ring-like structural maintenance of chromosomes (SMC) complex MukBEF folds the genome of Escherichia coli and related bacteria into large loops, presumably by active DNA loop extrusion. MukBEF activity within the replication terminus macrodomain is suppressed by the sequence specific unloader MatP. Here we present the complete atomic structure of MukBEF in complex with MatP and DNA as determined by electron cryomicroscopy (cryo-EM). The complex binds two distinct DNA double helices corresponding to the arm… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(42 citation statements)
references
References 91 publications
3
39
0
Order By: Relevance
“…Early molecular models for loop extrusion suggested that the SMC ring topologically embraces the DNA upon loading and during DNA loop extrusion. 31,40 More recently, also a pseudotopological 11,41,13 and nontopological loading 13,42 of the DNA were considered. The data from the current study provide unambiguous evidence for a nontopological mode for DNA loop extrusion, where DNA must bind externally to the SMC complex.…”
mentioning
confidence: 99%
“…Early molecular models for loop extrusion suggested that the SMC ring topologically embraces the DNA upon loading and during DNA loop extrusion. 31,40 More recently, also a pseudotopological 11,41,13 and nontopological loading 13,42 of the DNA were considered. The data from the current study provide unambiguous evidence for a nontopological mode for DNA loop extrusion, where DNA must bind externally to the SMC complex.…”
mentioning
confidence: 99%
“…ParC inhibits the MukBF ATPase (21), implying, given the folded conformation of MukB (23,24) and our crosslinking results, that ParC might interpose itself between the MukB hinge and neck regions and that this might disrupt the ATPase cycle, further suggesting that isolated MukB hinge might stimulate the MukBF ATPase in trans . This proved to be the case.…”
Section: Resultsmentioning
confidence: 81%
“…Mapping of MukB head and neck mutations to the MukBEF structures of Burmann et al (23). A, overall view of the head, neck and larynx regions of the MukBF dimer in the core MukBEF cryo-EM structure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter establishes the overall ring structure of the SMCC, and formation of the ATPase-ATP-ATPase "bridge" (shown in blue in Fig. 1B) can divide the ring into two compartments (25,28,61,62).…”
Section: Model Geometrymentioning
confidence: 93%